Quality of life for teenagers with social deprivation - Rusina, Svitlana (Psychosomatic Medicine and General Practice, 2018)
Background. Social instability, crisis «social neglect» and «social isolation» in teenagers is relevant because it impaired mental health and forms psychical disadaptation. All this thinks determines this investigate. Purpose. To investigate quality of life in socially depressed teenagers. Materials and methods. The results of experimental psychological research 100 teenagers with social depression and clinic-psychopathological, statistical methods was used. Results. The result of research quality of life in teenagers with social depressed was next : the most vulnerable for biological and social orphans was psychological and physical sphere, and for teenagers with social-maternal, socio-psychological and family depressed was environment and relationship. Conclusion. Socio-economic, medico-psychological factors have led to impairment quality of life in lest protected people – teenagers.